Franchise Contracts under Turkish Law: A Doctrinal Investigation - Ay, Yunus Emre (Universitas Muhammadiyah Yogyakarta, 2024)
Franchise contract refers to contract in which the franchisor gives the franchise system to the franchisee and in return, the franchisee is under certain obligations and pays a fee. Although franchise contracts have been very common in practice, nevertheless, these contracts are not regulated by any legislation in Turkey. This study examines franchise agreements in the light of Turkish law within the framework of doctrinal opinions. In the absence of specific legislation, this doctrinal research relies on secondary materials. It is found that franchise contract is commutative in nature which imposes mutual obligation on the contracting parties. The franchisor has the obligation to inform about the content of the franchise system in pre-contractual period, to provide the franchise system smoothly and to support the franchisee. The franchisee, on the other side, has the obligation to market the goods or services, to enjoy the franchise system, to tolerate supervision and to comply with instructions, to pay remuneration.